AB0765 CAN A 6-JOINT ULTRASOUND SCORE DIFFERENTIATE RHEUMATOID ARTHRITIS FROM PSORIATIC ARTHRITIS? A CROSS SECTIONAL STUDY. (2nd June 2020) - Figus, F.; Idolazzi, L.; Perić, P.; Zabotti, A.; Tinazzi, I.; Azzolin, I.; Montabone, E.; Sapundzhieva, T.; Batalov, A.; Todorov, P.; Karalilova, R.; Iagnocco, A.
Abstract : Background: Ultrasonography (US) is a well established technique both for diagnosis and follow up in Rheumatoid Arthritis (RA) and Psoriatic Arthritis (PSA) 1 . To date, there is no consensus regarding a standardized US evaluation of joint involvement by a validated score to be used for differential diagnosis. Objectives: 1) To differentiate the ultrasound features of patients affected by active RA or active PSA by using a 6-joints score 2 . 2) To analyze correlations between those findings and clinical patterns of PSA disease. Methods: 68 RA and 38 PSA patients (divided in two equal subgroups according to the clinical involvement i.e. polyarticular or oligoarticular) were enrolled in a multi-center cross-sectional study. All patients underwent clinical evaluation including demographic data, disease characteristics, laboratory test and tender/swollen joints count. SDAI and DAPSA were calculated in accordance to the disease and standard of care. The sonographic evaluation of wrists, II MCFs and knees, was performed using a multifrequency linear probe (13-18 MHz) with power Doppler (7.5 MHz, PRF500 Hz). High-end equipment was used and the scanning technique as well as the lesion assessment was previously agreed among the participants, who performed a consensus session 100 images. A validated ultrasound score 2, which included effusion, synovial hypertrophy and synovial hypervascularization at 6 joints sites was used. Those lesions were assessed according to OMERACT definitions and semi-quantitatively graded (0-3). By summing the scores obtained at each joint site and globally, a joint score for articular involvement, a score for the severity of each lesion and a global 6-joint score for all abnormalities were calculated. Results: Clinical evaluation showed no statistically significant differences between RA and PSA (table I). Ultrasound detected significant differences in the score of joint effusion (SE) (p<0.021), synovial hypertrophy (SH) (p<0.001) and Doppler signal (p<0.011) between oligoarticular PSA and RA. Significant differences in the joint score of II MCF (p<0.000) and wrist (p<0.032) were also found between oligoarticular PSA and RA. The global 6-joint score was 10, 88 in RA, 6, 05 in PSA oligoarticular, 16, 32 in PSA polyarticular. No differences were found between RA and polyarticular PSA. Conclusion: Ultrasound evaluation of 6 target joints might help to discriminate RA and PSA oligoarticular subset. The study of a limited number of joints is therefore a complementary tool to the clinic, fast and well integrated into the overall assessment of the arthritic patient. References: [1]Zabotti A. et al. Clin Exp Rheumatol. 2018; 36:519-525. [2]Perricone C et al. Rheumatology (Oxford) 2012; 51:866-73. Disclosure of Interests: Fabiana Figus: None declared, Luca Idolazzi: None declared, Porin Perić: None declared, Alen Zabotti Speakers bureau: Celgene, Janssen, Ilaria Tinazzi: None declared, Irene Azzolin: None declared, ERIKA MONTABONE: None declared, Tanya Sapundzhieva: None declared, Anastas Batalov: None declared, PLAMEN TODOROV: None declared, Rositsa Karalilova: None declared, Annamaria Iagnocco Grant/research support from: Abbvie, MSD and Alfasigma, Consultant of: AbbVie, Abiogen, Alfasigma, Biogen, BMS, Celgene, Eli-Lilly, Janssen, MSD, Novartis, Sanofi and Sanofi Genzyme, Speakers bureau: AbbVie, Alfasigma, BMS, Eli-Lilly, Janssen, MSD, Novartis, Sanofi